Pengaruh Ukuran Perusahaan, Kebijakan Hutang, Dan Profitabilitas Terhadap Nilai Perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia (BEI) Pada Tahun 2019 – 2022 - Putri Misbahul Hayat; Mintauli Debataraja (UNIVERSITAS RAHARJA, 2024)
Having clear company goals is one strategy for facing intense competition between companies. Maximizing company value is one of the elements that forms the goal of starting a business. Factors that can influence company value include company size, debt policy and profitability. The research method used in this research is a quantitative method, with the sampling method used is nonprobability sampling with a purposive sampling technique. From the results of the T test, company size (SIZE) partially has no effect on company value (PBV), debt policy (DER) partially has a positive and significant effect on company value (PBV) and profitability (ROE) partially has a positive and significant effect on value. company (PBV). Meanwhile, from the results of the F test, company size (SIZE), debt policy (DER) and profitability (ROE) simultaneously influence company value (PBV).